The syndromic deafness mutation G12R impairs fast and slow gating in Cx26 hemichannels - García, Isaac E. (J Gen Physiol, 2018)
Mutations in connexin 26 (Cx26) hemichannels can lead to syndromic deafness that affects the cochlea and skin. These mutations lead to gain-of-function hemichannel phenotypes by unknown molecular mechanisms. In this study, we investigate the biophysical properties of the syndromic mutant Cx26G12R (G12R). Unlike wild-type Cx26, G12R macroscopic hemichannel currents do not saturate upon depolarization, and deactivation is faster during hyperpolarization, suggesting that these channels have impaired fast and slow gating. Single G12R hemichannels show a large increase in open probability, and transitions to the subconductance state are rare and short-lived, demonstrating an inoperative fast gating mechanism. Molecular dynamics simulations indicate that G12R causes a displacement of the N terminus toward the cytoplasm, favoring an interaction between R12 in the N terminus and R99 in the intracellular loop. Disruption of this interaction recovers the fast and slow voltage-dependent gating mechanisms. These results suggest that the mechanisms of fast and slow gating in connexin hemichannels are coupled and provide a molecular mechanism for the gain-of-function phenotype displayed by the syndromic G12R mutation.